Gamification Pedagogy: Innovative Teaching Strategies to Increase Holistic Learning Engagement in the Classroom - Fadia Zahra Yuliannisa; Intan Robiatu Solihah; Euis Latipah; Neng Zuhrotu Diniah (COMPETITIVE: Journal of Education, 2026)
21st-century education demands innovative strategies to holistically increase student engagement in the classroom. One relevant approach is gamification pedagogy, which involves applying game design elements and principles within a learning context to stimulate intrinsic motivation and active participation. This article aims to analyze the potential of gamification pedagogy in enhancing students' cognitive, emotional, and social engagement, and its role in addressing 21st-century learning challenges. The method employed is a systematic literature review of various relevant scholarly publications. The study findings indicate that gamification effectively creates a dynamic and interactive learning environment, significantly boosts learning interest, and fosters critical thinking, collaboration, and self-directed learning skills, particularly for Generation Alpha. Therefore, gamification is recommended as an innovative pedagogical strategy to optimize student learning potential.